C-reactive protein, inflammation and coronary heart disease - Amit Kumar Shrivastava (The Egyptian Heart Journal, 2015)
Inflammation is widely considered to be an important contributing factor of the pathophysiology of coronary heart disease (CHD), and the inflammatory cascade is particularly important in the atherosclerotic process. In consideration of the important role that inflammatory processes play in CHD, recent work has been focused on whether biomarkers of inflammation may help to improve risk stratification and identify patient groups who might benefit from particular treatment strategies. Of these biomarkers, C-reactive protein (CRP) has emerged as one of the most important novel inflammatory markers. CRP an acute phase protein is synthesized by hepatocytes in response to proinflammatory cytokines, in particular interleukin-6. Many large-scale prospective studies demonstrate that CRP strongly and independently predicts adverse cardiovascular events, including myocardial infarction, ischemic stroke, and sudden cardiac death in individuals both with and without overt CHD. CRP is believed to be both a marker and a mediator of atherosclerosis and CHD. CRP plays a pivotal role in many aspects of atherogenesis including, activation of complement pathway, lipids uptake by macrophage, release of proinflammatory cytokines, induces the expression of tissue factor in monocytes, promotes the endothelial dysfunction and inhibits nitric oxide production. The commercial availability of CRP high sensitive assays has made screening for this marker simple, reliable, and reproducible and can be used as a clinical guide to diagnosis, management, and prognosis of CHD.